Cost-Effectiveness of Pembrolizumab Plus Chemotherapy Versus Pembrolizumab Monotherapy in Metastatic Non-Squamous and Squamous NSCLC Patients With PD-L1 Expression ≥ 50% - Liu, Qiao; Zhou, Zhen; Luo, Xia; Yi, Lidan; Peng, Liubao; Wan, Xiaomin; Tan, Chongqing; Zeng, Xiaohui (Frontiers in Pharmacology, 2022)
Objective To compare the cost-effectiveness of the combination of pembrolizumab and chemotherapy (Pembro+Chemo) versus pembrolizumab monotherapy (Pembro) as the first-line treatment for metastatic non-squamous and squamous non-small-cell lung cancer (NSCLC) with PD-L1expression ≥50%, respectively, from a US health care perspective. Material and Methods A comprehensive Makrov model were designed to compare the health costs and outcomes associated with first-line Pembro+Chemo and first-line Pembro over a 20-years time horizon. Health states consisted of three main states: progression-free survival (PFS), progressive disease (PD) and death, among which the PFS health state was divided into two substates: PFS while receiving first-line therapy and PFS with discontinued first-line therapy. Two scenario analyses were performed to explore satisfactory long-term survival modeling. Results In base case analysis, for non-squamous NSCLC patients, Pembro+Chemo was associated with a significantly longer life expectancy [3.24 vs 2.16 quality-adjusted life-years (QALYs)] and a substantially greater healthcare cost ($341,237 vs $159,055) compared with Pembro, resulting in an ICER of $169,335/QALY; for squamous NSCLC patients, Pembro+Chemo was associated with a slightly extended life expectancy of 0.22 QALYs and a marginal incremental cost of $3,449 compared with Pembro, resulting in an ICER of $15,613/QALY. Our results were particularly sensitive to parameters that determine QALYs. The first scenario analysis yielded lower ICERs than our base case results. The second scenario analysis founded Pembro+Chemo was dominated by Pembro. Conclusion For metastatic non-squamous NSCLC patients with PD-L1 expression ≥50%, first-line Pembro+Chemo was not cost-effective when compared with first-line Pembro. In contrast, for the squamous NSCLC patient population, our results supported the first-line Pembro+Chemo as a cost-effective treatment. Although there are multiple approaches that are used for extrapolating long-term survival, the optimal method has yet to be determined.